Impact of the Adriatic–Ionian bimodal oscillating system (BiOS) on the biodiversity patterns of the larval fish community in the north-eastern sector of the Strait of Sicily (central Mediterranean, Malta Channel) - Patti, Bernardo; Torri, Marco; Placenti, Francesco; Cuttitta, Angela (Frontiers in Earth Science, 2025)
Off the southern coast of Sicily, the frontal region south of Cape Passero (Malta Channel) provides favorable conditions for fish larvae survival and development and hosts a biodiversity hotspot for larval assemblages. In this area, the analysis of ichthyoplankton data collected during 16 oceanographic summer surveys, carried out every year over the period from 2001 to 2016, shows a cyclical pattern in the yearly average larval biodiversity, which appears to be linked to the alternating cyclonic/anticyclonic surface circulation of the North Ionian Gyre (NIG), associated with the Adriatic–Ionian bimodal oscillating system (BiOS). Specifically, the cyclonic mode of NIG, by enhancing the advection of Modified Atlantic Water (MAW) toward the southern Levantine Basin and reducing its deflection toward the Adriatic, is supposed to intensify the frontal thermohaline structure, thus inducing higher retention/survival rates for fish larval stages and, definitively, resulting in higher biodiversity. The association between total fish larval density and biodiversity with available environmental data, namely, satellite-derived sea surface temperature (SST) and in situ temperature, salinity, and surface current speed, corroborates this hypothesis. Finally, the observed changes in the biodiversity of the larval fish community would result from increased/reduced retention time for fish larvae (and accordingly, slower/faster larval dispersal) across the frontal area, as induced by the alternating cyclonic–anticyclonic modes of NIG. These results pave the way for future investigations on the role of surface circulation patterns in the dynamics of fish populations, with special emphasis on the effects of retention processes on fish larval stages.